ESL and content teachers’ collaboration - Amanda Giles; Bedrettin Yazan (Universitas Katolik Indonesia Atma Jaya, 2019)
This paper reviews the earlier studies to synthesize the benefits and challenges of ESL and content teachers’ collaboration and discusses Amanda’s recent experiences of collaboration in a middle school in the Southeastern U.S. Previous studies document the collaborative benefits (DelliCarpini, 2018), which include teacher learning, increased ESL students’ participation, and strengthened professional partnerships. However, ESL and content teachers’ collaboration has yet to become a routine teaching practice in the U.S., particularly in secondary mainstream classrooms, because of the reported challenges (Dove & Honigsfeld, 2018), such as teachers’ incompatible personalities and beliefs (Arkoudis, 2003), conflicting schedules (Peercy, Ditter, & DeStefano, 2016), inconsistent administrative support (Villa, Thousand, Nevin, Liston, 2005), and the ESL teacher’s relegated role compared to the content teacher (Ahmed Hersi, Horan, & Lewis, 2016). In order for ESL and content teachers’ collaboration to be a pathway for equitable learning outcomes for ESL students, educational stakeholders, namely content teachers, ESL teachers, and school administrators, need to share responsibility for planning for and teaching ESL students. This begins with school administrators who can foster a culture of collaboration, and content and ESL teachers who can take steps to build and strengthen collaborative partnerships. More specific recommendations are discussed in the conclusion.